2022
DOI: 10.1186/s12870-022-03445-8
|View full text |Cite
|
Sign up to set email alerts
|

SPL9 mediates freezing tolerance by directly regulating the expression of CBF2 in Arabidopsis thaliana

Abstract: Background Freezing stress inhibits plant development and causes significant damage to plants. Plants therefore have evolved a large amount of sophisticated mechanisms to counteract freezing stress by adjusting their growth and development correspondingly. Plant ontogenetic defense against drought, high salt, and heat stresses, has been extensively studied. However, whether the freezing tolerance is associated with ontogenetic development and how the freezing signals are delivered remain unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…For example, a recent study indicated that low temperature also induced the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE 9 (SPL9) gene in Arabidopsis plants. SPL9 may directly bind to the promoter of one of the CBF genes, leading to increased freezing tolerance [ 39 ]. Results in Betula luminifera indicated that certain SPLs may also interact with DELLA proteins, influencing the processes regulated by GA [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study indicated that low temperature also induced the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE 9 (SPL9) gene in Arabidopsis plants. SPL9 may directly bind to the promoter of one of the CBF genes, leading to increased freezing tolerance [ 39 ]. Results in Betula luminifera indicated that certain SPLs may also interact with DELLA proteins, influencing the processes regulated by GA [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…What are the effects of the particular spatial location of chromatin to the NPC on gene transcription and epigenetic regulation under harsh conditions? (3) Plant ontogenetic defense against abiotic and biotic stresses has been extensively studied [ 119 , 120 , 121 ]. Studies have indicated that NPCs functions in plant developmental transitions.…”
Section: Future Perspectivementioning
confidence: 99%
“…Except for ABA signaling, microRNAs (miRNAs) have been considered one of the most important signaling molecules in response to various stresses and in the regulation of developmental processes in plants (Singh et al, 2021; Wu et al, 2009; Zhao et al, 2022). Of them, miR156 and miR159 interact with each other to regulate plant development (Guo et al, 2017); and they are both altered by abiotic stresses and mediate the stress pathways via independent ways (Cui et al, 2015; Ge et al, 2018; Reyes & Chua, 2007; Singh et al, 2021; Zhao et al, 2022). miR156 targets SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE (SPL) genes to regulate developmental transitions and abiotic stresses, including drought, salt and cold (Arshad et al, 2017; Cui et al, 2015; Gou et al, 2011; Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Of them, miR156 and miR159 interact with each other to regulate plant development (Guo et al, 2017); and they are both altered by abiotic stresses and mediate the stress pathways via independent ways (Cui et al, 2015; Ge et al, 2018; Reyes & Chua, 2007; Singh et al, 2021; Zhao et al, 2022). miR156 targets SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE (SPL) genes to regulate developmental transitions and abiotic stresses, including drought, salt and cold (Arshad et al, 2017; Cui et al, 2015; Gou et al, 2011; Zhao et al, 2022). ABA induces miR159 in an ABI3‐dependent manner, it renders plants hyposensitive to ABA by suppressing the expression of its targets, MYB33 and MYB101 (Reyes & Chua, 2007).…”
Section: Introductionmentioning
confidence: 99%